A phase II prospective open-label escalating dose trial of recombinant interleukin-11 in mild von Willebrand disease - RAGNI, M. V.; JANKOWITZ, R. C.; CHAPMAN, H. L.; MERRICKS, E. P.; KLOOS, M. T.; DILLOW, A. M.; NICHOLS, T. C. (Haemophilia : the official journal of the World Federation of Hemophilia, 2008)
von Willebrand factor (VWF) is a multimeric glycoprotein that mediates platelet adhesion and is decreased in von Willebrand disease (VWD). 1‐8 deamino‐d‐arginine vasopressin (DDAVP), the most common treatment for VWD, is limited by tachyphylaxis and inconvenience, and in 20% of the patients, unresponsiveness. Recombinant human interleukin‐11 (rhIL‐11), a gp‐130 signalling cytokine with haematopoietic and anti‐inflammatory activity, increases VWF antigen and its activity in heterozygous VWF+/− mice and dogs. To determine the biological efficacy and safety of rhIL‐11 in non‐bleeding human subjects with mild VWD, we conducted a phase II prospective open‐label trial of rhIL‐11 at 10, 25 and 50 μg kg−1 subcutaneously (s.c.), given daily for 7 days in nine subjects with mild VWD. VWF and factor VIII (FVIII) levels increased gradually and progressively after s.c. rhIL‐11, which was sustained through 7 days of dosing to 1.5‐ to 3‐fold over baseline. Following intravenous DDAVP, 0.3 μg kg−1, on day 7 there was a further boost in VWF and FVIII levels, suggesting that the mechanism of rhIL‐11 differs from that of DDAVP. Platelet VWF mRNA expression measured by quantitative PCR increased from two‐ to eightfold over baseline, suggesting that the mechanism of rhIL‐11 effect may be upregulation of VWF mRNA. VWF and FVIII levels returned to baseline by day 14. rhIL‐11 was well tolerated with less than grade‐1 hypertension, hypokalaemia and fluid retention. Recombinant IL‐11 increases VWF levels in humans with mild VWD, justifying future clinical trials to determine its potential in preventing or reducing bleeding in this patient population.